Impoundments affect fish reproduction regardless of reproductive strategy. Issue 4 (December 2016) - Angulo‐Valencia, Mirtha A.; Agostinho, Angelo A.; Suzuki, Harumi I.; da Luz‐Agostinho, Karla D. G.; Agostinho, Carlos S.
Abstract: Major changes to local river habitats, after impoundment, are expected to restrict the reproductive activity of fishes with migratory strategies, although the changes are not expected to have relevant effects on fishes with other strategies. The reproductive activity of fishes with different reproductive strategies was evaluated along a longitudinal gradient before, and after, the formation of a reservoir on the Tocantins River (Tocantins State, Brazil). Samples were collected at six sites distributed along 80‐km stretch of the reservoir (R1 to R6 in the upstream–downstream direction) before and after the impoundment. The highest mean values of the reproductive activity index (RAI), considering all species in the river phase, were recorded for the intermediate segments (R4). The reproductive activity was classified as intense at the two sites located further upstream (R2 and R1). The highest mean RAI value after impoundment was observed for the site further upstream (R1). The reproductive activity was classified as intense, however, at every site, except for R6. Regardless of the reproductive strategy, mean RAI values were higher in this phase at site R1, particularly for long‐distance migratory species (LDM). The most lacustrine area (R6) was only relevant for the group of species with parental care. For non‐long‐distance migratory species, without parental care, the reproductive activity was intense at every site, except for R6. Overall, after the impoundment, the fish species tended to seek more lotic environments to spawn, including the riverine zone of the reservoir and side tributaries, regardless of the reproductive strategy. The results of this study provide evidence that impoundments affect the reproduction of the fish, independent of the reproductive strategy, although the intensity of the effect is different for each group.